A miniaturized seven-electrode conductivity and temperature integrated sensor. Issue 1 (1st February 2022) - Sun, Wei; Guo, Fengxiang; Chai, Xu; Hu, Ding; Zhang, Xueyu; Xu, Mingxia; Wang, Yibao; Wang, Shaoyan; Wu, Xiaofan; Qu, Chuang; Gai, Zhigang
Abstract: Marine environmental monitoring technology is the support of marine development, and its development level and innovation capability have become important criteria for measuring a country's marine science and technology indicators. In order to meet the application demand of large-scale and high-density deployment of marine observation network, a planar open seven-electrode conductivity and platinum resistance temperature integrated sensor is developed by using Micro Electro Mechanical System(MEMS) technology, combined with semiconductor micro and nano precision processing technologies such as mask lithography and physical sputtering. The measurement principle, probe design preparation, packaging and calibration method of this conductivity temperature sensor are presented. By calibrating and fitting the measurement data of this sensor, good measurement accuracy results were obtained. The miniaturized conductivity temperature sensor has the advantages of small size, low power consumption, low cost and high accuracy of probe processing, high batch consistency, and fully meets the application requirements of marine observation network.